Penerapan Metode Diskusi Kelompok Dalam Pelajaran Pendidikan Agama Islam (PAI) Kelas XII di SMAN 3 Lubuk Basung - Vela Yulianita; Muhiddinur Kamal; Afrinaldi Afrinaldi; Supratman Zakir (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to describe the method of implementing education in Islamic religious education lessons, such as the steps for implementing the discussion method and the obstacles faced by teachers in applying the discussion method in Islamic religious education lessons in the classroom. The author conducted this research at SMAN 3 Lubuk Basung. The approach used is a qualitative approach. With descriptive method. So the type of research is descriptive. The research subjects were Islamic religious teachers and students. The data collection techniques are observation, interviews and documentation, the data analysis technique used is data selection, data presentation and conclusion drawing and the data validation technique is the data triangulation technique. The results of this research explain that the application of the discussion method has proceeded in accordance with the application of discussion but is still not in accordance with existing theories, such as in the preparation step the teacher did not determine the type of discussion that would be used and prepared something related to the technical implementation of the discussion. The steps in carrying out the discussion were not in accordance with the established rules. In the closing section there are several steps that have not been implemented, namely the teacher has not yet reviewed the discussion that has been delivered by the speaker in the discussion. And the obstacles that the author found in implementing the discussion method were such as requiring a long time for discussion, uneven student activity, facilities not supporting it, and teachers not yet mastering the theories in applying the discussion method optimally. In conclusion, the teacher's understanding and knowledge of the theories The implementation of the discussion method needs to be improved further for the smooth implementation of discussions in PAI lessons in the future.